DOI: 10.22215/etd/2017-12220
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization and Modelling of a Heat Pump Water Heater

Abstract: Canada plays a leading role in the initiative to divert energy sources from greenhouse gas (GHG) emissive power sources to renewable and sustainable energy sources. Through the Clean Energy Act, Canada is subjected to introduce a reduction in electricity demand by 66%, and GHG emission reduction by 80%, from the levels achieved in 2007, by 2020. This thesis investigated the use of heat pump water heater technology to assist in the reduction of GHG emissions and energy in domestic water heating for the resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…It was concluded that increasing the water temperature in the tank resulted in a lower COP, and increasing the air temperature increased the COP. In Khalaf's testing [39], it was noted that increasing the relative humidity from 20% to 70% at an air temperature of 20°C led to a negligible increase in heat delivery and compressor energy consumption, thus had little effect on the unit's performance. In the present research, however, it was found that the relative humidity did have a larger effect at higher air temperatures.…”
Section: Heat Recovery Ventilatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was concluded that increasing the water temperature in the tank resulted in a lower COP, and increasing the air temperature increased the COP. In Khalaf's testing [39], it was noted that increasing the relative humidity from 20% to 70% at an air temperature of 20°C led to a negligible increase in heat delivery and compressor energy consumption, thus had little effect on the unit's performance. In the present research, however, it was found that the relative humidity did have a larger effect at higher air temperatures.…”
Section: Heat Recovery Ventilatorsmentioning
confidence: 99%
“…In order to model the heat pump water heater, a new heat pump type developed by Khalaf [39] was used (Type 240). This type includes a domestic hot water tank (Type 534) and a wrap-around condenser coil.…”
Section: Heat Pump Typementioning
confidence: 99%
See 3 more Smart Citations